The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.clim.2008.03.459
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of autoreactive antigen-specific CD4+ T cells in autoimmune diabetes after pancreas transplantation

Abstract: CD4+ T cells specific for the diabetes-associated autoantigen GAD65 were analyzed using peripheral blood samples after pancreas transplantation in subjects with T1D with clinical evidence of recurrent autoimmune diabetes. MHC class II tetramers facilitated the identification and cloning of antigenspecific autoreactive cells, which were found at several time points over a multiyear span, in spite of chronic immunosuppression of the subjects. Comparisons of TCR clonotypes by cDNA sequencing revealed that identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 21 publications
(23 reference statements)
2
57
0
1
Order By: Relevance
“…Persistence of autoantibodies did not confer increased risk. While previous studies have noted associations of autoantibodies with graft failure 25, 29, our study is the first to link autoantibodies specifically to biopsy‐confirmed T1D recurrence, and in our own ongoing studies these are being linked to autoimmune T cell responses (Table S1A) 11, 42.…”
Section: Discussionmentioning
confidence: 61%
“…Persistence of autoantibodies did not confer increased risk. While previous studies have noted associations of autoantibodies with graft failure 25, 29, our study is the first to link autoantibodies specifically to biopsy‐confirmed T1D recurrence, and in our own ongoing studies these are being linked to autoimmune T cell responses (Table S1A) 11, 42.…”
Section: Discussionmentioning
confidence: 61%
“…The recognition of the role of islet autoreactive CD4+ T cells [22,23] and CD8+ T cells [27,30] on beta-cell destruction, as well as all the targets of humoral activity [28] , may lead to other treatment opportunities. Novel therapies, namely targeting proinsulin-reactive CD8+ T cells, were recently pro-posed as a potential therapeutic approach [31] .…”
Section: Resultsmentioning
confidence: 99%
“…The Miami group has tried to treat autoimmune relapse in pancreas transplants with anti-lymphocyte (anti-B and/or anti-T cell) therapies [21][22][23] . After a transient response in a few cases, autoimmune activity has recurred within a short period of time.…”
Section: Immunosuppression and Autoimmunitymentioning
confidence: 99%
“…This phenomenon of selective destruction of beta cells was also observed in recipients of cadaveric pancreatic grafts [36] and in recipients of islet allografts [37] without evidence of alloimmune rejection [34][35][36]. Further studies strongly suggested that recurrence of T1D autoimmunity was due to autoreactive, antigenspecific memory CD8 + and CD4 + T cells after islet and pancreas transplantation [37][38][39][40]. In a multicenter, randomized, double-blind, placebo-controlled clinical trial of recent onset T1D patients, treatment with alefacept, preserved their C-peptide secretion, reduced insulin use and hypoglycemic events, and induced favorable immunologic profiles at one year, even after one year of termination of therapy.…”
Section: Successesmentioning
confidence: 76%